PEMBELAJARAN PAI BERBASIS ICT - Suci Amalia (Jurnal Al Wahyu, 2023)
This research aims to explore and apply an Islami Religious Education (PAI) learning model based on Information and Communication Technology (ICT). This teaching method utilizes technology such as online platforms, multimedia and digital resources to increase the interactivity and effectiveness of PAI learning. This research includes an analysis of the impact of using ICT on understanding religious concepts, student involvement, and time efficiency in the context of religious learning. It is hoped that the results of this research can contribute to the development of PAI learning strategies that are in line with technological developments, improve the quality of religious education, and prepare students to face global challenges with a better understanding of religion.